Expanding Labour’s Horizons: Union Organizing and Strategic Change in Canada - Yates, Charlotte A. B. (Charlotte Alyce Bronwen) (Just Labour: A Canadian Journal of Work and Society, 2002)
How can unions arrest membership decline in an increasingly chilly climate? Unions across Canada have arrived at a common answer to this question; unions need to organize the unorganized, in particular reaching out to women, youth and people of colour. After a brief discussion of who is being organized by unions, this article turns to a discussion of innovations in union organizing strategies, including the virtue of rank and file activists and the B.C. Organizing Institute. The next challenge for unions is to keep newly organized workers as members. This depends on adequate representation of these members’ interests and opportunities for their participation in union affairs. The paper critically evaluates union efforts at reform of internal structures and collective bargaining practices. While organizing alone cannot secure the future of unions, it is a critical part of the process of the renewal of labour power.